Correcting Presbyopia With Autofocusing Liquid-Lens Eyeglasses - Karkhanis, Mohit U.; Ghosh, Chayanjit; Banerjee, Aishwaryadev; Hasan, Nazmul; Likhite, Rugved; Ghosh, Tridib; Kim, Hanseup; Mastrangelo, Carlos H. (IEEE transactions on biomedical engineering, 2022)
Objective: Presbyopia, an age-related ocular disorder, is characterized by the loss in the accommodative abilities of the human eye. Conventional methods of correcting presbyopia divide the field of view, thereby resulting in significant vision impairment. We demonstrate the design, assembly and evaluation of autofocusing eyeglasses for restoration of accommodation without dividing the field of view. Methods: The adaptive optics eyeglasses comprise of two variable-focus liquid lenses, a time-of-flight range sensor and low-power, dual microprocessor control electronics, housed within an ergonomic frame. Subject-specific accommodation deficiency models were utilized to demonstrate high-fidelity accommodative correction. The abilities of this system to reduce accommodation deficiency, its power consumption, response time, optical performance and MTF were evaluated. Results: Average corrected accommodation deficiencies for 5 subjects ranged from -0.021 D to 0.016 D. Each accommodation correction calculation was performed in ∼67 ms which consumed 4.86 mJ of energy. The optical resolution of the system was 10.5 cycles/degree, and featured a restorative accommodative range of 4.3 D. This system was capable of running for up to 19 hours between charge cycles and weighed ∼132 g. Conclusion: The design, assembly and performance of an autofocusing eyeglasses system to restore accommodation in presbyopes has been demonstrated. Significance: The new autofocusing eyeglasses system presented in this article has the potential to restore pre-presbyopic levels of accommodation in subjects diagnosed with presbyopia.